(untitled) (CIPEEX, 2022)
THIS STUDY AIMS TO INVESTIGATE THE STATE OF WELL-BEING AND QUALITY OF LIFE, BEFORE AND AFTER A PULMONARY REHABILITATION INTERVENTION, IN PATIENTS WHO SURVIVED COVID-19 AND HAD SOME COMPLICATIONS. THE WHOQOL-BREF WAS USED TO ASSESS QUALITY OF LIFE, AND THE LIFE SATISFACTION AND POSITIVE AND NEGATIVE AFFECT SCALES WERE USED TO ASSESS WELL-BEING. BEFORE THE INTERVENTION, LIFE SATISFACTION WAS AT A LOWER LEVEL (M=23.09; SD=6.25), AS WAS QUALITY OF LIFE. AFFECTS, ON THE OTHER HAND, WERE MEDIAN IN THEIR OUTCOME. THE RESULTS SUGGEST THAT SOME ACTIVITIES DEVELOPED IN REHABILITATION, AS WELL AS THE RETURN TO SOCIALIZATION AND A ROUTINE, STRENGTHEN THE RECOVERY OF PHYSICAL HEALTH, PROMOTING IMPROVEMENT IN DIFFERENT DIMENSIONS OF LIFE.